Vitamins, supplements and COVID-19: a review of currently available evidence - Lauren Speakman; Sarah Michienzi; Melissa Badowski (BioExcel Publishing Ltd, 2021)
Background: In the midst of the COVID-19 pandemic, there has been an information overload of health data (both accurate and inaccurate) available to the public. With vitamins and supplements being readily accessible, many have turned to using them in an effort to combat the virus. The purpose of this review was to analyse clinical trials regarding vitamins and supplements for the treatment of COVID-19 infections. Methods: Articles were identified through a literature search utilizing online databases and bibliographic review. Results: A total of seven articles were identified for review. All articles evaluated the use of vitamins and supplements for the treatment of COVID-19. Drug therapies included oral vitamin D, intravenous and oral vitamin C, oral vitamin D/magnesium/vitamin B12, oral zinc, oral combination zinc/ascorbic acid, and intravenous alpha-lipoic acid. The end points of each study varied, including the Sequential Organ Failure Assessment score, mortality, rate of intensive care unit (ICU) admissions, negativity of COVID-19 tests, oxygen requirements, and symptom burden. Conclusion: Of the vitamins and supplements that were studied, vitamin D presented the most promising data demonstrating significant decreases in oxygen requirements, need for ICU treatment, SARS-CoV-2 RNA test positivity, and mortality. All of these benefits were exhibited in hospitalized patients. Other vitamins and supplements that were evaluated in studies did not demonstrate any statistically significant benefits. Common shortcomings of the articles included generally small sample sizes, varying sites of study (which could determine the virus variant), a lack of standard of care as background therapy, and utilization of doses that were higher than standard.